Analysis of GPS Data from An Antarctic Ice Stream - Dach, R.; Beutler, G.; Gudmundsson, Hilmar (Springer, 2008)
Temporal variations in the flow of an active ice stream are analyzed using GPS data collected over a period of two months at six different locations. The diameter of the network is about 60 km. The ice stream moves with a velocity of about one meter per day. The kinematic data are processed using three different strategies: zero-difference network solution, Precise Point Positioning, and double-difference network solution with resolved carrier phase ambiguities. The solutions are compared with regard to the quality of the resulting coordinate time series. Special attention is paid to the positional accuracy as a function of temporal frequency for these different analysis methods as the overall aim of the measurements is to estimate temporal variability in ice flow.